Pendekatan Service-Dominant Logic dalam Menjelaskan Analisis Faktor Antecedent dengan Peran Fintech sebagai Moderasi pada Customer Retention - Christy, Caroline; Kurniawati, Kurniawati; Masnita, Yolanda (Dinasti Review, 2026)
Abstract: The rapid growth of digital banking and financial technology has transformed service delivery in the banking industry, making customer retention a critical issue for sustaining competitiveness. SDL emphasizes that value is created through interactions between service providers and customers, highlighting the importance of empathy, value co-creation, value in use, and customer satisfaction.This study proposes and tests a conceptual framework based on SDL to analyse the effects of empathy, value co-creation, value in use, and customer satisfaction on customer retention, with fintech as a moderating variable. Data was collected from customers of KBMI 4 banks in Indonesia. This study extends customer retention literature by integrating value in use and value co-creation into a unified empirical model and by positioning fintech as a moderating factor in the satisfaction–retention relationship. The results indicate that empathy enhances value co-creation and value in use, which subsequently increase customer retention, while fintech strengthens the impact of customer satisfaction on retention. Banks are encouraged to enhance empathetic service and optimize fintech capabilities to improve long-term customer retention. Abstract: The rapid growth of digital banking and financial technology has transformed service delivery in the banking industry, making customer retention a critical issue for sustaining competitiveness. SDL emphasizes that value is created through interactions between service providers and customers, highlighting the importance of empathy, value co-creation, value in use, and customer satisfaction.This study proposes and tests a conceptual framework based on SDL to analyse the effects of empathy, value co-creation, value in use, and customer satisfaction on customer retention, with fintech as a moderating variable. Data was collected from customers of KBMI 4 banks in Indonesia. This study extends customer retention literature by integrating value in use and value co-creation into a unified empirical model and by positioning fintech as a moderating factor in the satisfaction–retention relationship. The results indicate that empathy enhances value co-creation and value in use, which subsequently increase customer retention, while fintech strengthens the impact of customer satisfaction on retention. Banks are encouraged to enhance empathetic service and optimize fintech capabilities to improve long-term customer retention